KAJIAN NILAI LAHAN PERTANIAN DISEKITAR JALAN TOL MANADO-BITUNG (STUDI KASUS DESA TUMALUNTUNG KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA) - Pinontoan Jennifer Juliana; Theodora Maulina Katiandagho; Paulus Adrian Pangemanan (Sam Ratulangi University, 2019)
This research aims to identify (1) the difference in the value of agricultural land before and after becoming the Manado-Bitung toll road and (2) describe the social and economic changes of landowners in tumaluntung village. The study was conducted on the object of the constructions of the Manado-Bitung toll road in the village of Tumaluntung. The time of the study from august to November 2017 and continued in May until June 2019. The method used in this research is descriptive method presented in tabular form. Determination of the sample using the (purposive sampling) method. Primary data used in this study were obtained through interviews with 15 landowners. The secondary data obtained from the Tumaluntung village office, internet through google scholar to get articles from various scientific journals and theses from other tertiary institutions related to the topic of research on the value of agricultural land. The results of the study show that (1) the value of agricultural land before becoming the Manado-Bitung toll road is higher than the value of land after the toll road has been built. (2) improve social status (making current landowners better at meeting needs because land compensation money is used by landowners to be deposited into bank as investment capital such as boarding houses, bakeries, livestock business chiken, showroom, restaurant cars for purchasing capital for cars used for transportation service..*eprm*